2007
DOI: 10.1515/bc.2007.101
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Kupffer cell-dependent signaling in T3-induced hepatocyte proliferation in vivo

Abstract: Thyroid hormone-induced calorigenesis triggers liver oxidative stress with concomitant TNF-alpha production by Kupffer cells and up-regulation of gene expression. Considering that cyclin-dependent kinase-2 (CDK-2) performs essential functions for cellular proliferation, our aim was to test the hypothesis that l-3,3',5-triiodothyronine (T(3)) stimulates liver cell proliferation by upstream mechanisms involving CDK-2 expression dependent on Kupffer cell signaling. T(3) administration induced a calorigenic respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…TH transporter and receptor expression in Kupffer cells have not yet been studied. TH also increases the production of TNFα by Kupffer cells (Valencia et al 2004, Fernandez et al 2005, 2007b. TNFα produced by Kupffer cells results in liver NFκB activation (Valencia et al 2004).…”
Section: Effects Of Extracellular Thyroid Hormone Levels On Macrophagmentioning
confidence: 99%
See 1 more Smart Citation
“…TH transporter and receptor expression in Kupffer cells have not yet been studied. TH also increases the production of TNFα by Kupffer cells (Valencia et al 2004, Fernandez et al 2005, 2007b. TNFα produced by Kupffer cells results in liver NFκB activation (Valencia et al 2004).…”
Section: Effects Of Extracellular Thyroid Hormone Levels On Macrophagmentioning
confidence: 99%
“…This is thought to be mediated via Kupffer cells, which demonstrate hyperplasia, increased phagocytic capacity, increased ROS generation and tumour necrosis factor α (TNFα) production in response to T 3 administration in vivo (Fig. 2B) (Tapia et al 1997, Valencia et al 2004, Fernandez et al 2005, 2007b. Kupffer cell activation by T 3 triggers a cascade of responses in the liver including increased TNFα and interleukin-6 (IL-6) levels, which lead to the activation of liver STAT3 phosphorylation and nuclear factor kappa-B (NFκB) DNA binding.…”
Section: Thyroid Hormone Metabolism In Tissue-resident Macrophagesmentioning
confidence: 99%
“…This contention was evaluated in the 1-h ischemia-20-h reperfusion model, which elicited substantial liver damage with increased serum aspartate aminotransferase and TNF-a levels, higher liver oxidative stress status, loss of the DNA binding capacity of NF-jB and STAT3 implying loss of cytoprotective potential, and enhancement in AP-1 activation (78) as a major determinant of hepatotoxicity (79). These changes were normalized by a single dose of T 3 given 48 h before the IR protocol (78), a hormetic effect that was sensitive to the antioxidant N-acetylcysteine (80) or the Kupffer cell inactivator GdCl 3 given prior to T 3 , with enhanced hepatocyte proliferation compensating for liver cells lost due to IR-induced hepatocellular necrosis (68). Alternate hormetic responses induced by T 3 may involve (i) the transcriptional upregulation of uncoupling protein genes affording lower mitochondrial ROS generation (23,30) and export of peroxidized unsaturated fatty acid anions (81); (ii) acceleration of substrate cycles such as ATP cycling that increases mitochondrial oxidative phosphorylation and lowers ROS production, and/or NADPH cycling that favors antioxidants reduction, thus promoting ROS scavenging (82); and (iii) activation of the Nrf2 defense pathway (unpublished), upregulating antioxidant proteins and phase 2 detoxifying enzymes and transporters (83,84).…”
Section: Hormetic Nature Of Kupffer Cell-dependent Redox Upregulationmentioning
confidence: 99%
“…In vivo hormone administration triggers liver CDK-2 expression and cellular proliferation through a cascade associated with JNK phosphorylation and AP-1 activation. 34 A recent study has demonstrated that T3 also has anticarcinogenic effects. 35 Moreover, other authors have reported changes in genes involved in apoptosis and cell cycle progression, 6 h after T3 administration.…”
Section: The Technique Shows Normal Cells (Bright Green Chromatin) Amentioning
confidence: 99%